Pemanfaatan Limbah Plastik menjadi Paving Block di Kelurahan Industri Tenayan, Kota Pekanbaru - Nazhifah, Nazhifah; Dari, Wulan; Marliana, Nana; Putra M, Rachel Pramana; Ilham, Robby Aprilo; Salsabilla, Putri Annisa; Madina, Virginaya Flara; Sari, Imelia; Harefa, Cahayu Prildana; Farhan, M Alif; Ramadani, Cici; Hutabarat, Veronica Wijaya; Yohanes, Yohanes; Rafil, Rafil; Salsabila, Sofia Putri; Munandar, Putra Aris; Wahyuni, Sri; Lukman, Luvenia Andrius; Pratama, Zikra Mulya; Habeahan, Hosea; Abdillah, Marco; Ependi, Rinto; Wijaya, Sidiq Nugraha; Wanda, Wanda (Universitas Pahlawan Tuanku Tambusai, 2025)
Community Service Program (KKN) is a form of student service to the community with the aim of providing solutions to the increasing problem of plastic waste management in Industri Tenayan Village. Improperly managed plastic waste has the potential to pollute the environment and reduce the quality of life of the community. This KKN program aimed to raise public awareness of plastic waste management and provide practical skills through training in the production of environmentally friendly paving blocks. The methods used included counseling on the impact of plastic waste, socialization of waste utilization concepts, workshops on paving block production, and practical training involving 30 local participants. Evaluation was carried out using pre-test and post-test to measure knowledge improvement and through observation of paving block production results. The results showed an increase in participants’ knowledge by 85%, technical skills by 78%, and the production of 50 paving blocks that are ready for use and have potential market value. This program contributed to reducing plastic waste volume while creating new business opportunities for the community.